BrABF3 promotes flowering through the direct activation of CONSTANS transcription in pak choi. (6th May 2022) - Zhang, Changwei; Zhou, Qian; Liu, Wusheng; Wu, Xiaoting; Li, Zhubo; Xu, Yuanyuan; Li, Ying; Imaizumi, Takato; Hou, Xilin; Liu, Tongkun
SUMMARY: Drought stress triggers the accumulation of the phytohormone abscisic acid (ABA), which in turn activates the expression of the floral integrator gene CONSTANS ( CO ), accelerating flowering. However, the molecular mechanism of ABA‐induced CO activation remains elusive. Here, we conducted a yeast one‐hybrid assay using the CO promoter from Brassica campestris (syn. Brassica rapa ) ssp. chinensis (pak choi) to screen the ABA‐induced pak choi library and identified the transcription activator ABF3 (BrABF3). BrABF3, the expression of which was induced by ABA in pak choi, directly bound to the CO promoter from both pak choi and Arabidopsis. The BrABF3 promoter is specifically active in the Arabidopsis leaf vascular tissue, where CO is mainly expressed. Impaired BrABF3 expression in pak choi decreased BrCO expression levels and delayed flowering, whereas ectopic expression of BrABF3 in Arabidopsis increased CO expression and induced earlier flowering under the long‐day conditions. Electrophoretic mobility shift assay analysis showed that BrABF3 was enriched at the canonical ABA‐responsive element–ABRE binding factor (ABRE–ABF) binding motifs of the BrCO promoter. The direct binding of BrABF3 to the ABRE elements of CO was further confirmed by chromatin immunoprecipitation quantitative PCR. In addition, the induction of BrCO transcription by BrABF3 could be repressed by BrCDF1 in the morning. Thus, our results suggest that ABA could accelerate the floral transition by directly activating BrCO transcription through BrABF3 in pak choi. Significance Statement: We found for the first time that BrABF3 is the fourth group of transcription factors that directly bind to the CO promoter to promote flowering.